Quantitative trait loci and antagonistic associations for two developmentally related traits in the drosophila head - Norry, Fabian Marcelo (2017)
In insects, some developmentally related traits are negatively correlated. Here, we mapped Quantitative Trait Loci (QTL) for traits of eye size and head capsule, in an intercontinental set of recombinant inbred lines (RILs) of Drosophila melanogaster. Composite interval mapping identified QTL on all major chromosomes. Two negatively correlated traits (size of eyes and between-eyes distance) were influenced by one QTL that appeared to be antagonistic between the traits (QTL cytological range is 25F5-30A6), consistent with a negative genetic correlation between these traits of the head capsule. Comparisons of QTL across traits indicated a nonrandom distribution over the genome, with a considerable overlap between some QTL across traits. Developmentally-related traits were influenced by QTL in a pattern that is consistent both with 1) the sign of the genetic correlation between the traits and 2) a constraint in the micro-evolutionary differentiation in the traits.